CVD whiskerization treatment process for the enhancement of carbon fiber composite flexural strength - Abdul Rashid, Suraya; Vargis, Christina; Yunus, Robiah; Shamsudin, Suryani (Universiti Putra Malaysia Press, 2008)
Carbon fiber composite performance can be enhanced by applying an optimum level of fiber surface treatment such as whiskerization. The main objectives of this study were to conduct whiskerization through carbon nanotube (CNT)-coating of carbon fiber via chemical vapour deposition (CVD) at various conditions (temperature and hydrogen flow rate) and to investigate the enhancement in flexural strength of composites fabricated from these CNT-coated carbon fibers. The results indicated that CNTs were able to grow onto the carbon fibres with the highest amount of whiskerization occurring for samples nearest the reactant gas inlet of the CVD Rig. Various whiskerization behaviours were observed at different reaction temperatures and flow rates. From flexural tests, it was found that whiskerization treatment on carbon fibers increases the flexural strength of its composites between 44-122%.